Infotechnologies in the knowledge of venomous animal species present in the republic of Angola - Armiñana-García, Rafael (2024)
The objective of this work was to propose the website “Poisonous Fauna Present in the Republic of Angola” to contribute to the knowledge of poisonous animals that can cause harm to the health of certain sectors of the Angolan population and Cuban internationalists who provide services in that country. For the development of the research, methods of collecting and processing the information collected were used, highlighting the survey and the interview. The population is made to coincide with the sample, which is intentional and not probabilistic and was made up of 40 foreign students who were studying in Cuba, in addition to 10 collaborators who were preparing to carry out a mission in the Republic of Angola. The proposal was subjected to the criteria of experts who assessed it as pertinent and the site was validated both in the Republic of Angola and in the Republic of Cuba, with excellent results.